2015
DOI: 10.1007/s11663-015-0456-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Granule Size on the Kinetics of Electrochemical Reduction of SiO2 Granules in Molten CaCl2

Abstract: As a fundamental study to develop a new process for producing solar-grade silicon, the effect of granule size on the kinetics of the electrochemical reduction of SiO 2 granules in molten CaCl 2 was investigated. SiO 2 granules with different size ranges were electrolyzed in molten CaCl 2 at 1123 K (850 °C). The reduction kinetics was evaluated on the basis of the growth rate of the reduced Si layer and the behavior of the current during electrolysis. The results indicated that finer SiO 2 granules are more fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Once forming a core (SiO 2 )-shell (Si) structure for a SiO 2 particle, the reaction front would relocate from the particle surface to the inner part, and the reduction rate would decrease because of potential drop and more difficult diffusion of O 2− ions. [39][40][41] In case of incomplete reduction, pure Si can be recovered via H 2 O rinse to remove residual CaCl 2 and subsequent HF acid rinse to remove unreacted SiO 2 . Figure 5 illustrates the process of a single SiO 2 particle transforming from precursor to product.…”
Section: Resultsmentioning
confidence: 99%
“…Once forming a core (SiO 2 )-shell (Si) structure for a SiO 2 particle, the reaction front would relocate from the particle surface to the inner part, and the reduction rate would decrease because of potential drop and more difficult diffusion of O 2− ions. [39][40][41] In case of incomplete reduction, pure Si can be recovered via H 2 O rinse to remove residual CaCl 2 and subsequent HF acid rinse to remove unreacted SiO 2 . Figure 5 illustrates the process of a single SiO 2 particle transforming from precursor to product.…”
Section: Resultsmentioning
confidence: 99%
“…To that end, dependence of the reduction rate on SiO 2 particle size has been studied. Granules were used as the precursors with the dimensions from 0.1 mm to 2.0 mm . It was found that finer granules were more favorable for the reaction rate due to lower contact resistance with the Si substrate.…”
Section: Electrochemical Production Of Si In Molten Cacl2 From Sio2mentioning
confidence: 99%
“…Granules were used as the precursors with the dimensions from 0.1 mm to 2.0 mm. 41 It was found that finer granules were more favorable for the reaction rate due to lower contact resistance with the Si substrate. Porosity of the produced structure facilitated diffusion of produced oxygen (9).…”
Section: Electrochemical Production Of Si In Molten Cacl 2 From Siomentioning
confidence: 99%
“…From this starting point, we proposed the direct electrolytic reduction of solid SiO 2 in molten CaCl 2 at the relatively low temperature of 1123 K. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In contrast to traditional molten salt electrolysis, the cathodic reduction of SiO 2 proceeds through a solid-state reaction. We performed a series of studies in which we investigated the reduction of SiO 2 plates, 10,11 sintered SiO 2 pellets, 12 and stratified SiO 2 granules, [22][23][24][25][26] and clarified the reaction mechanisms involved. The purities of the obtained Si powders were also measured, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%